Partial Confinement Utilization for Rectangular Concrete Columns Subjected to Biaxial Bending and Axial Compression - Abd El Fattah, A. M.; Rasheed, Hayder A.; Al-Rahmani, A. H. (My University, 2017)
The prediction of the actual ultimate capacity of confined concrete columns requires partial confinement utilization under eccentric loading. This is attributed to the reduction in compression zone compared to columns under pure axial compression. Modern codes and standards are introducing the need to perform extreme event analysis under static loads. There has been a number of studies that focused on the analysis and testing of concentric columns. On the other hand, the augmentation of compressive strength due to partial confinement has not been treated before. The higher eccentricity causes smaller confined concrete region in compression yielding smaller increase in strength of concrete. Accordingly, the ultimate eccentric confined strength is gradually reduced from the fully confined value f(cc) (at zero eccentricity) to the unconfined value f(c)(1) (at infinite eccentricity) as a function of the ratio of compression area to total area of each eccentricity. This approach is used to implement an adaptive Mander model for analyzing eccentrically loaded columns. Generalization of the 3D moment of area approach is implemented based on proportional loading, fiber model and the secant stiffness approach, in an incremental-iterative numerical procedure to achieve the equilibrium path of P-epsilon and M-phi response up to failure. This numerical analysis is adapted to assess the confining effect in rectangular columns confined with conventional lateral steel. This analysis is validated against experimental data found in the literature showing good correlation to the partial confinement model while rendering the full confinement treatment unsafe.
Citation: Abd El Fattah, A. M., Rasheed, H. A., & Al-Rahmani, A. H. (2017). Partial Confinement Utilization for Rectangular Concrete Columns Subjected to Biaxial Bending and Axial Compression. International Journal of Concrete Structures and Materials, 11(1), 135-149. doi:10.1007/s40069-016-0178-z
Keywords: Rectangular Columns; Partial Confinement; Combined Loading; Eccentricity; High-Strength Concrete; Stress-Strain Relationship